Development of Curriculum Concept and Gurukul Education System in Nepal - Acharya, Tank (Journal of Musikot Campus, 2025)
This study analyzes the structure, characteristics, and educational impact of the traditional Gurukul education system in Nepal and compares it with the modern curriculum. The main objective of this research, conducted through library research method, is to reconsider modern education in the context of Gurukul-based ethics, discipline, and spiritual education. According to the research results, the Guru-Shishya tradition of Gurukul is found to have special emphasis on holistic development, moral teaching, and spiritual discipline. The Gurukul curriculum was flexible, orally transmitted, and deeply related to religious and philosophical education. When compared to the modern curriculum, Gurukul education seems to have placed more emphasis on character building and life experience, while modern education seems to focus more on academic achievement and structured knowledge transmission. According to the conclusion of this study, incorporating the moral values, personal guidance, and spiritual practices of Gurukul education in modern education can be helpful in enhancing the quality of education and overall student development. More action research is needed on this topic, so that the original teaching tradition can be integrated into the modern curriculum.